Apaf‐1 interacting protein, a new target of microRNA‐146a‐3p, promotes prostate cancer cell development via the ERK1/2 pathway. (27th March 2022) - Wang, Nan; Li, Rou; Jia, Huizhen; Xie, Hui; Liu, Chi; Jiang, Shan; Zhang, Ke; Lin, Ping; Yu, Xiaoguang
Abstract: The Apaf‐1 interacting protein (APIP), a ubiquitously expressed antiapoptotic molecule, is aberrantly expressed and of great significance in various cancers. However, little is known regarding the potential value and underlying mechanisms of APIP in prostate cancer. Here, we demonstrated that APIP expression is significantly upregulated in prostate cancer cell lines. APIP overexpression promoted tumor cell proliferation and migration and induced extracellular regulated protein kinases 1/2 (ERK1/2) activation. Pharmacological inhibition of ERK1/2 signaling reversed APIP‐induced increase in cell proliferation and migration induced by APIP overexpression. Expression of APIP was hampered by miR‐146a‐3p. A dual luciferase reporter gene assay identified the regulatory relationship between APIP and miR‐146a‐3p in prostate cancer, suggesting that APIP is a direct target of miR‐146a‐3p. miR‐146a‐3p reduced cell proliferation and migration in prostate cancer. Furthermore, miR‐146a‐3p inhibited ERK1/2 activation. Application of an ERK1/2 inhibitor reversed the increase in cell proliferation and migration induced by miR‐146a‐3p inhibition. In summary, this study focused on the role of APIP in regulating cell growth and migration and proposes a theoretical basis for APIP as a promising biomarker in prostate cancer development.